Subsistence practices in Phoenicia and beyond: faunal investigations at Tell el-Burak, Lebanon (c. 725–350 BCE). (2nd September 2022) - Vermeersch, Shyama; Starkovich, Britt M.; Orsingher, Adriano; Kamlah, Jens
Abstract : Agricultural practices in Iron Age Phoenicia are an understudied field of research. The most recently excavated faunal evidence from Tell el-Burak, a coastal agricultural domain linked to either Sidon or Sarepta, will increase our understanding of this topic. This paper provides the first diachronic and detailed analysis of the Late Iron Age and Persian period faunal data from Tell el-Burak, and investigates the subsistence practices of its people during the late 8th to mid-4th centuries BCE. The diet of its inhabitants mainly consists of caprines, while a high percentage of donkeys and cattle remains coincide with the peak of winemaking activities at the site. The results from Tell el-Burak are then compared with faunal data from other sites in the territory traditionally known as Phoenicia, as well as with faunal data from the neighbouring regions of the Levant. The comparisons show differences between the northern and southern Levant and similarities between southern Phoenicia and the southern Levant.